Nota sobre la noción de amor sui en Tomás de Aquino : reflexividad de la voluntad y subjetividad humana - Beroch, María Aracoeli (Sapientia, 2017)
The article proposes to revise the meaning of amor sui in some of the main Thomistic texts where the term is mentioned, in order to determine whether it may contribute to a Thomistic theory of subjectivity. In the first place, the reflexivity of the will is explained as an intellectual appetite that has the capacity to turn back on its own act (voluntas vult se velle). This characteristic of the faculty enables one to affirm that man turns back upon himself, not only by means of the intellect but also by means of the will itself. Secondly, the notion of amor/dilectio sui is considered: love tends toward a double object; that is, the good that is desired, and the person for whom this good is desired. In such a way, it is possible to highlight the importance of the subject acting, who, in the case of amor sui, returns toward himself, loving himself and maintaining the love for himself even in relation to other men and to God.